The Impact of Ewom, Brand Attitude, and Brand Image on Sugar Product Purchase Intentions - Kaliya, Isabella; Muliyani, Nani (Yayasan Gema Bina Nusantara, 2024)
This research aims to analyze whether there is an influence between Ewom, brand attitude, and brand image on purchase intentions. The researchers collected data by observing, conducting literature studies, and distributing questionnaires to the respondents. From the results of the research that has been carried out, it was found that electronic word of mouth (eWoM) was proven to have a significant influence on the intention to purchase the product. This indicates that the influence of reviews and recommendations via electronic platforms has a positive impact on consumer purchasing interest. Second, brand attitude also has a significant influence on purchase intentions, indicating that consumers' attitudes towards the brand play a crucial role in forming the desire to purchase the product. However, the findings show that brand image does not have a significant influence on purchase intention, indicating that brand image does not directly influence consumer purchase intention. Finally, the research results show that the combination of eWoM, brand attitude, and brand image attitude together have a significant influence on purchase intention for sugar products. These findings provide an important contribution to understanding the factors that influence consumer decisions to purchase certain products in the context of the sugar industry.